2008
DOI: 10.1682/jrrd.2007.08.0120
|View full text |Cite
|
Sign up to set email alerts
|

Restoring hearing symmetry with two cochlear implants or one cochlear implant and a contralateral hearing aid

Abstract: Abstract-With today's technology and the demonstrated success of cochlear implantation, along with expanded candidacy criteria, the opportunity to provide optimal hearing to both ears for individuals with severe-to-profound hearing loss is greater than ever. This article reviews the advantages of binaural hearing and the disadvantages of hearing with only one ear or hearing with two ears with significantly different sound thresholds. A case study is presented that demonstrates the benefit of bimodal hearing (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 88 publications
2
67
0
Order By: Relevance
“…Researchers have shown that listeners with normal hearing are sensitive to ITDs of 10 to 15µs (Firszt et al, 2008). However, studies have reported relatively poor sensitivity to…”
Section: Interaural Time Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have shown that listeners with normal hearing are sensitive to ITDs of 10 to 15µs (Firszt et al, 2008). However, studies have reported relatively poor sensitivity to…”
Section: Interaural Time Differencesmentioning
confidence: 99%
“…Because CI users are more sensitive to ILDs than ITDs, ILDs have been considered the primary cue for sound source localization (Firszt et al, 2008).…”
Section: Interaural Level Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…When the nonimplanted ear does not provide any benefit despite acoustic amplification, bilateral cochlear implantation is the alternative suggestion (Tyler et al 2003;van Hoesel & Tyler 2003). Many studies have shown the benefits of bimodal rehabilitation (Ching et al 2004;Firszt et al 2008;Potts et al 2009;Sucher & McDermott 2009) or bilateral cochlear implantation Schleich et al 2004;Long et al 2006;Litovsky et al 2009;Loizou et al 2009;van Schoonhoven et al 2013) as compared with monaural listening with only one cochlear implant (CI). However, what the best solution would be between bimodal rehabilitation and bilateral cochlear implantation for each particular patient remains a difficult clinical decision.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid and EAS are names derived by the manufacturer, Cochlear and MED-EL, respectively. Individuals using these multiple hearing modalities compared with use of a CI alone may demonstrate measurable improvements in speech perception both in quiet and in noise (Ching, Incerti, & Hill, 2004;Ching, van Wanrooy, & Dillon, 2007;Dettman et al, 2004;Firszt, Reeder, & Skinner, 2008;Flynn & Schmidtke, 2004;Gantz & Turner, 2003;Gstoettner et al, 2004;Most, Gaon-Sivan, Shpak, & Luntz, 2012;Mowry et al, 2012;Potts, Skinner, Litovsky, Strube, & Kuk, 2009;Straatman, Rietveld, Beijen, Mylanus, & Mens, 2010;Tuner et al, 2008a;Turner, Reiss, & Gantz, 2008b), sound localization (Ching et al, 2004(Ching et al, , 2007Firszt, et al, 2008;Flynn & Schmidtke, 2004;Potts et al, 2009), music perception (Bartov & Most, 2014;Flynn & Schmidtke, 2004;Mowry et al, 2012;Turner et al, 2008b), and voice recognition (Flynn & Schmidtke, 2004), as well as subjective benefits of access to binaural hearing and sound quality from combined acoustic and electric hearing (Ching et al, 2004;Firszt et al, 2008;Flynn & Schmidtke, 2004;Potts et al, 2009). However, the benefit of the addition of amplification to CI use is variable across individuals, particularly for speech perception, and an effective clinical protocol for programming of multiple hearing modalities has not yet been determined, as not every parameter has been investigated (Blamey & Saunders, 2008;Dorman, Spahr, Loizou, Dana, & Schmidt, 2005;Heo, Lee, & Lee, 2013;…”
mentioning
confidence: 99%